Percutaneous Transiliac–Transsacral Screw Fixation of Sacral Fragility Fractures Improves Pain, Ambulation, and Rate of Disposition to Home. Issue 9 (September 2018) - Walker, J. Brock; Mitchell, Sean M.; Karr, Sean D.; Lowe, Jason A.; Jones, Clifford B.
Abstract : Objective: To determine whether percutaneous transiliac–transsacral screw fixation improves pain, ambulation, length of stay, and the rate of disposition to home in patients with sacral fragility fractures. Design: Retrospective cohort study. Setting: Single academic Level 1 trauma center. Patients/Participants: Elderly patients who presented with an isolated sacral fragility fracture between August 2015 and August 2017. Of the 41 patients included in the study, 16 were treated operatively and 25 were treated nonoperatively. Intervention: Percutaneous transiliac–transsacral screw fixation. Main Outcome Measurements: Pain, ambulation, length of stay, complications, and disposition. Results: Patients treated operatively reported a greater improvement in pain as measured by the visual analog scale (3.9 vs. 0.6 points, P < 0.001). At the time of discharge, 100% of surgically treated patients were able to ambulate compared with 72% in the nonoperative group ( P = 0.03). Average distance ambulating at the time of discharge was higher in the operative group (95 vs. 35 ft, P < 0.01). Length of stay was similar between the 2 groups (3.6 days in operative group vs. 4.2 days in nonoperative group, P = 0.5). Of the patients treated operatively, 75% were discharged to home compared with only 20% in the nonoperative group ( P < 0.001). There were no complications related to surgery. Conclusions: Percutaneous transiliac–transsacral screw fixation of sacral fragility fractures lessens pain, improves ambulation, and increases the rate of disposition to home. Further investigation is needed to determine if surgical fixation provides benefit regarding medium- and long-term outcome variables. Level of Evidence: Therapeutic Level III. See Instructions for Authors for a complete description of levels of evidence.